Evaluating Alternate Methods of Determining the Antimicrobial Efficacy of Contact Lens Care Products against Acanthamoeba Trophozoites - Allison Campolo; Paul Shannon; Monica Crary (Pathogens, 2021)
Acanthamoeba keratitis (AK) is a serious ocular infection caused by a ubiquitous free-living amoeba, Acanthamoeba. This infection often results in extensive corneal damage and blindness, and is notoriously difficult to cure. While Acanthamoeba is an abundant organism, AK is most associated with contact lens hygiene noncompliance and inadequate contact lens care (CLC) disinfection regimens. Thus, accurate and timely antimicrobial efficacy testing of CLC solutions is paramount. Published methods for antimicrobial efficacy testing of Acanthamoeba trophozoites requires 14 days for results. Presently, alternate and/or rapid methods for evaluating CLC products rarely demonstrate equivalent results compared to commonly-reported methods. Propidium iodide is a cellular stain that can only bind to cells with damaged outer membranes. We evaluated propidium iodide staining as an alternative method for determining the relative antimicrobial efficacy of 11 different CLC products against Acanthamoeba trophozoites. Following exposure to a CLC product, the fluorescence intensity of propidium iodide in an Acanthamoeba population demonstrated a strong correlation to the log reduction determined by established, growth-based Acanthamoeba testing used to evaluate the antimicrobial efficacy of CLC products. Thus, propidium iodide was found to be an effective rapid tool for determining cell death in Acanthamoeba trophozoites following exposure to CLC solutions.